2016
DOI: 10.18632/oncotarget.9687
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial SIRT1 prevents adverse arterial remodeling by facilitating HERC2-mediated degradation of acetylated LKB1

Abstract: Aims-SIRT1 exerts potent activity against cellular senescence and vascular ageing. By decreasing LKB1 protein levels, it promotes the survival and regeneration of endothelial cells. The present study aims to investigate the molecular mechanisms underlying SIRT1-mediated LKB1 degradation for the prevention of vascular ageing.Methods and Results-Co-immunoprecipitation assay demonstrated that SIRT1, via its amino-terminus, binds to the DOC domain of HERC2 [HECT and RLD domain containing E3 ubiquitin protein ligas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 55 publications
0
42
0
Order By: Relevance
“…41 Additionally, an in vitro deacetylation assay also showed that SIRT1 seemed not to deacetylate LKB1 peptide containing acetylated lysine 48. 42 SIRT1 may regulate AMPK by other mechanisms. For instance, SIRT1 regulates secretion of adipokines such as adiponectin, 43 which activates AMPK through a CaMKKβ-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…41 Additionally, an in vitro deacetylation assay also showed that SIRT1 seemed not to deacetylate LKB1 peptide containing acetylated lysine 48. 42 SIRT1 may regulate AMPK by other mechanisms. For instance, SIRT1 regulates secretion of adipokines such as adiponectin, 43 which activates AMPK through a CaMKKβ-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, another molecular mechanism underlying the preventive effect of SIRT1 against endothelial senescence and vascular aging has been demonstrated, showing that SIRT1 prevents endothelial senescence by downregulating acetylation of stress-responsive serine/threonine liver kinase B1 (LKB1) via HERC2, a giant scaffold protein, and E3 ubiquitin ligase (Fig. 3) (13). In aged arteries or senescent ECs, an increased nuclear accumulation of acetylated LKB1 is observed when SIRT1 expression and function are lost with concomitant irreversible alterations of vascular stiffness, blood vessel wall, and adverse arterial remodeling, suggesting that the SIRT1/HERC2/LKB1 complex fine tunes the crosstalk between endothelial and VSMCs to maintain vascular homeostasis (13).…”
Section: Sirt1 In Cell Senescence and Aging Processesmentioning
confidence: 99%
“…3) (13). In aged arteries or senescent ECs, an increased nuclear accumulation of acetylated LKB1 is observed when SIRT1 expression and function are lost with concomitant irreversible alterations of vascular stiffness, blood vessel wall, and adverse arterial remodeling, suggesting that the SIRT1/HERC2/LKB1 complex fine tunes the crosstalk between endothelial and VSMCs to maintain vascular homeostasis (13). Conversely, SIRT1 overexpression and increased LKB1deacetylation prevented the EC senescence in vitro, as well as the stress-induced senescence in mice (221).…”
Section: Sirt1 In Cell Senescence and Aging Processesmentioning
confidence: 99%
“…Donato et al previously reported that Sirt1 expression is reduced in endothelial cells obtained from arteries of older human adults (64 ± 1 years) compared to those from younger adults (25 ± 1 years), and reduced endothelial Sirt1 expression with aging may be related to endothelial dysfunction through the impairment of NO production from eNOS [47]. Recently, Bai et al demonstrated the molecular mechanisms underlying the preventive effect of endothelial senescence and vascular aging [48]. Sirt1 prevents endothelial senescence by enhancing Liver kinase B1 (LKB1) degradation by its deacetylation, which causes an interaction with HECT and RLD domain containing E3 ubiquitin protein ligase 2(HERC2), a giant scaffolding protein and E3 ubiquitin ligase.…”
Section: Introductionmentioning
confidence: 99%